Brain activation during dual-task processing is associated with cardiorespiratory fitness and performance in older adults - Wong, Chelsea N.; Chaddock-Heyman, Laura; Voss, Michelle W.; Burzynska, Agnieszka Z.; Basak, Chandramallika; Erickson, Kirk I.; Prakash, Ruchika S.; Szabo-Reed, Amanda N.; Phillips, Siobhan M.; Wojcicki, Thomas; Mailey, Emily L.; McAuley, Edward; et al. (Frontiers in Aging Neuroscience, 2015)
Higher cardiorespiratory fitness is associated with better cognitive performance and enhanced brain activation. Yet, the extent to which cardiorespiratory fitness-related brain activation is associated with better cognitive performance is not well understood. In this cross-sectional study, we examined whether the association between cardiorespiratory fitness and executive function was mediated by greater prefrontal cortex activation in healthy older adults. Brain activation was measured during dual-task performance with functional magnetic resonance imaging in a sample of 128 healthy older adults (59-80 years). Higher cardiorespiratory fitness was associated with greater activation during dual-task processing in several brain areas including the anterior cingulate and supplementary motor cortex (ACC/SMA), thalamus and basal ganglia, right motor/somatosensory cortex and middle frontal gyrus, and left somatosensory cortex, controlling for age, sex, education, and gray matter volume. Of these regions, greater ACC/SMA activation mediated the association between cardiorespiratory fitness and dual-task performance. We provide novel evidence that cardiorespiratory fitness may support cognitive performance by facilitating brain activation in a core region critical for executive function.